2007
DOI: 10.1007/s00249-007-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic restacking of Escherichia Coli P-pili

Abstract: P-pili of uropathogenic Escherichia coli mediate the attachment to epithelial cells in the human urinary tract and kidney and therefore play an important role in infection. A better understanding of this mechanism could help to prevent bacteria from spreading but also provides interesting insights into molecular mechanics for future nanotech applications. The helical rod design of P-pili provides an efficient design to withstand hydrodynamic shear forces. The adhesive PapG unit at the distal end of the P-pilus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 45 publications
6
44
1
Order By: Relevance
“…On the other hand, it has been shown that the FimH-1M bond lifetime, assessed with force feedback AFM and flow-chamber experiments, is highest at 40 pN. [46] This suggests that the bond strength of FimH is about 40 pN under physical conditions, which supports the value reported by Lugmaier et al [48] …”
supporting
confidence: 59%
See 1 more Smart Citation
“…On the other hand, it has been shown that the FimH-1M bond lifetime, assessed with force feedback AFM and flow-chamber experiments, is highest at 40 pN. [46] This suggests that the bond strength of FimH is about 40 pN under physical conditions, which supports the value reported by Lugmaier et al [48] …”
supporting
confidence: 59%
“…Lugmaier et al [48] found recently that an adhesin of P pili PapG binds to a glycolipid galabiose receptor with a force of 49 pN and has a bond length of 0.7 AE 0.15 nm. In another study the specific adhesin of type 1 pili, FimH, that binds to mannose-presenting surfaces was found to have a force of only 1.7 pN.…”
mentioning
confidence: 98%
“…During the study, type IV pili were shown to have the same constant force plateaus associated with a nanospring-like mechanism; this may be explained by the fracturing of internal amino acid bonds and the unravelling of the three-dimensional structure to resist the increase in mechanical force. This model is consistent with the previous interpretations of Gram-negative pili structure [87][88][89]. In a similar study, strains of Lactococcus lactis were immobilized onto polyethyleneimine (PEI)-coated cantilever, and adhesion to a pig gastric mucin-coated substrate was characterized [90].…”
Section: Single-cell Force Spectroscopysupporting
confidence: 90%
“…This is a bond whose lifetime decreases with increased force, and this bond can withstand forces in AFM experiments up to 49 pN [67]. The interaction is weak enough to allow rolling behaviour of bacteria for quick spreading, but strong enough to initiate destacking of the PapA rod superhelical structure.…”
Section: Preventing Growth Of the Pilus With Pilicidesmentioning
confidence: 98%